ANALISIS FINANCIAL DISTRESS PADA PEMERINTAH PROVINSI GORONTALO TAHUN 2014-2018 - Pangku, Mutiara; Radjak, Lukfiah Irwan (JSAP : Journal Syariah and Accounting Public, 2021)
This research was conducted at the Regional Financial and Asset Agency of Gorontalo Province. The purpose of this study is to obtain answers to problems that have been formulated, to analyze financial risks to the government of Gorontalo Province. This study uses binary logistic regression method where the dependent variable financial distress is dummy and only has two possible outcomes, yes and no. From the results of research conducted partially on the independent variables, namely regional financial independence, local revenue, regional expenditure and solvency have no positive effect on the dependent variable financial distress. Meanwhile, simultaneously the independent variables of financial independence, local revenue, regional expenditure and solvency have a positive effect on the variables tied to financial distress